MUSLIMS AND VIOLENCE - Zerari, Fathi (European Scientific Journal, ESJ, 2013)
This paper tries to explain the relationship between Muslims' problems and violence in the light of a clear distinction between Islam and Islamic political thought. This research emphasizes on the fact that Koran and Sunnah aim at guiding mankind to the right path of knowing and worshipping God; they are not political treatises; Islam could live without a Muslim State even before the instauration of the prophet's State; nowadays, millions of Muslims live under the rule of non Muslim governments or Muslim governments that do not enforce the Islamic law, yet Islam continues to flourish; hence, no Islamic political thought, albeit useful and justified at a certain time, place, or circumstances is to be sanctified because that will certainly lead to a political blockage which could yield violence.